2021
DOI: 10.1111/cts.12993
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selenium on thyroid autoimmunity and regulatory T cells in patients with Hashimoto’s thyroiditis: A prospective randomized‐controlled trial

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium,provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 48 publications
(95 reference statements)
3
53
0
5
Order By: Relevance
“…For example, Se (100 µg/day for 6 months) significantly reduced the level of antithyroid peroxidase antibodies when administered in newly diagnosed and previously untreated HT patients with euthyroidism or subclinical hypothyroidism living in a Polish area with low Se status [ 87 ]. Moreover, administration of 200 μg/day Se yeast tablets for at least 6 months in HT patients improved thyroid autoantibodies and thyroid function by increasing the antioxidant activity [ 88 ]. The “SETI study” showed that short-course SeMet supplementation was associated with a normalization of serum TSH levels, which is maintained for 6 months after Se withdrawal in 50% of patients with subclinical hypothyroidism, due to chronic autoimmune thyroiditis [ 89 ].…”
Section: Selenium and Autoimmune Thyroiditis (Ait)mentioning
confidence: 99%
“…For example, Se (100 µg/day for 6 months) significantly reduced the level of antithyroid peroxidase antibodies when administered in newly diagnosed and previously untreated HT patients with euthyroidism or subclinical hypothyroidism living in a Polish area with low Se status [ 87 ]. Moreover, administration of 200 μg/day Se yeast tablets for at least 6 months in HT patients improved thyroid autoantibodies and thyroid function by increasing the antioxidant activity [ 88 ]. The “SETI study” showed that short-course SeMet supplementation was associated with a normalization of serum TSH levels, which is maintained for 6 months after Se withdrawal in 50% of patients with subclinical hypothyroidism, due to chronic autoimmune thyroiditis [ 89 ].…”
Section: Selenium and Autoimmune Thyroiditis (Ait)mentioning
confidence: 99%
“…Inflammatory response is a vital mechanism of H9N2 AIV pathogenicity [ 50 ]. Previous studies have found that selenium does not only affect the secretion of specific cytokines by phagocytes [ 51 ], but also directly acts on lymphocytes to enhance their function [ 52 , 53 ]. IL-1β and IFN-γ are linked with the initiation and regulation of cellular immune responses [ 54 , 55 ], whereas IL-6 (pro-inflammatory cytokine) is associated with the final maturation of B lymphocytes into antibody-secreting plasma cells [ 56 ] and development of T cell memory to influenza virus [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Selenium deficiency, an element that reduces oxidative stress, may affect the function of regulatory T lymphocytes in cAITD, as well as contribute to reduced concentrations of anti-thyroid antibodies and improved thyroid function [ 38 ]. Available reviews and meta-analyzes of different publications show that the use of routine selenium supplementation in AITD raises many doubts and seems to be justified only in the case of confirmed selenium deficiency [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%